Analisis Kesulitan Guru Dalam Mengimplementasikan Kurikulum Merdeka Belajar di SD Negeri Lamkrak Kabupaten Aceh Besar - Fajriah, Fajriah; Maulidar, Maulidar; Julia, Putry (Journal of Technology and Literacy in Education, 2024)
The implementation of the independent curriculum is still a confusion for some schools, teachers, and students. Likewise, what happened at SD Negeri Lamkrak, Aceh Besar Regency, the teachers did not fully understand and master how to implement learning in the implementation of the independent learning curriculum at the primary school level. So through this research, it aims to find out the implementation of the independent learning curriculum and the factors that cause teacher difficulties in implementing the independent learning curriculum at Lamkrak State Elementary School, Aceh Besar Regency. This research uses a qualitative descriptive method. The research subjects were 2 people, namely class I teachers and class IV teachers. Data collection techniques using observation sheets and interview guidelines. The data analysis technique uses the Miles and Huberman model which consists of Data Collection, Data Reduction, Data Display, and Conclusion Drawing/Verification. The results showed that the implementation of the independent learning curriculum has been running for about 2 years, but the implementation is still carried out in stages, namely only for classes I and IV while classes II, III, V and VI are still implementing the 2013 Curriculum. The observation results obtained a percentage of 80%, almost all items observed in the implementation of the independent curriculum still have many obstacles for teachers. The factors causing teacher difficulties are (1) lack of facilities and infrastructure, such as limited classes, no library, no science laboratory, language laboratory, computer laboratory; (2) lack of teacher competence in technology, there are still many teachers who do not master technology, such as the use of leptop, infocus and internet network; (3) lack of references available at school, such as teacher's manuals, student books, teaching aids and other media that support independent curriculum learning.